Design and Build a Motorcycle Security Controller Using the IoT-Based GPS Tracking Method - Afif Dimyati; Dwi Hadidjaja Rasjid (Procedia of Engineering and Life Science, 2021)
Motor vehicle theft cases still often occur around us, this happens because there is still a lack of security systems in motorized vehicles that only use ignition keys and key covers, where weaknesses in standard security systems like this have been understood by motor vehicle theft perpetrators. to do the action. To overcome this, a motorized vehicle security system was created using the IOT-based GPS tracking method to prevent and make it easier to retrieve a stolen motorized vehicle. So far, most motorcycle safety devices are still physically secure, for example a solution commonly used by motorized vehicle owners by adding safety locks to discs, chaining and so on, but owners often forget to install locks, or vehicle alarms. The result of this research is the production of a controller design tool, motorcycle safety and GPS tracking to provide information on the last location of motorized vehicles and can control remotely based on iot. which has been experienced by motorized vehicle users.